Ethno-Pedagogical Module: A Theoretical Exploration of Knowledge Transmission in Ethnobiological Systems - Rexhepi, Besnik; Bajrami, Ani (Three E Science Institute, 2025)
The vertical transmission of ethnobiological knowledge across generations is crucial in preserving biodiversity and sustaining biocultural diversity. However, the mechanisms underpinning this process remain insufficiently studied. This paper introduces the